Significações da revelação do diagnóstico para o adolescente que tem HIV/AIDS: possibilidades para enfermagem - Brum, Crhis Netto de (2013)
The aim of this study was to understand the meaning of the revelation of the diagnosis of human immunodeficiency virus (HIV) and acquired immunodeficiency syndrome (AIDS) adolescents. Qualitative and phenomenological investigation, based on the theoretical-methodological referential of Martin Heidegger. Field step was developed from November 2011 to February 2012, at the Infectious Diseases Service of Santa Maria University Hospital (SMUH), Rio Grande do Sul, Brazil. As a way of access the being, we used phenomenological interview and medical records data collection. It contemplated 12 adolescents that have HIV/AIDS, from 13 to 19 years old. Field step was concomitant with the analysis which enabled to reach the meaning sufficiency. Ethical aspects were respected according the Resolution 196/1996. Data analysis was based on two heideggerian methodical moments: 1) vague and median comprehension pointed to the adolescent that diagnosis disclosure means to know it before anybody tell them, even without understand it, until the family and/or health professionals explain it. They know how virus transmission was and that they need treatment. In the being, being scared and fearful, after understanding they get used to it and accept it. Not telling people and being scared of the reaction if anybody finds out. Having limits and rules for having something others don t. Accepting taking medicine and, with time, getting used to it and learning how to take care of themselves. Being a normal person, the different is the virus, having to take medicine and go to the hospital. 2) interpretative comprehension unveiled the being-a-teenager-who-experienced-the-revelation-of-the- diagnosis-of-HIV/AIDS, keep him/herself as everyone are and want him/her to be. Decayed on his/her quotidian, prisoned on his/her talking about received and passed information about his/her serological condition, curious for not knowing about his/her health situation and on the ambiguity of perceiving him/herself normal and feeling different. Once that, on the facticity of having HIV/aids he/she unveiled occupied with having to maintain the treatment. On the dominating solicitude of family members he/she took medicine because they gave it to him/her. However, liberating solicitude stabilishes itself when family members and/or health professionals explained that treatment is for their health, that way the the being-a-teenager-who-experienced-the-revelation-of-the-diagnosis-of-HIV/AIDS preoccupies in taking care of him/herself. The comprehension of the living of the being-a-teenager-who-experienced-the-revelation-of-the-diagnosis-of-HIV/AIDS unveil the need to incorporate the biological dimension to the existential dimension on the movement of disclosuring. The nurse has the prospect of enabling the movement of existential authenticity when the impersonality decadent enable the being-a-teenager-who-experienced-the-revelation-of-the-diagnosis-of-HIV/AIDS if (un) cover amid its potential, facilities, difficulties and limits on the disclosure.